SYNTHESIS OF MAGNETIC COMPOSITE OF IRON COMPOUNDS/CARBON NANOTUBES IN CHEMICAL VAPOR DEPOSITION - Teguh Endah Saraswati; Oktaviana Dewi Indah Prasiwi; Abu Masykur; Miftahul Anwar (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
The chemical vapor deposition (CVD) synthesis of magnetic carbon nanotubes (mCNT) using carbon dioxide/carbon catalyst has been successfully carried out in various pressures. The temperatures were set at 800° C for 10 minutes reaction time. Nitrogen (N2) gas in 20 Torr was flown in followed by ethanol vapor until the final pressure reached 80 and 100 Torr without added air, and 180 Torr with added air. The formation of mCNT was confirmed by shifted X-ray diffraction (XRD) peak of graphite from 26.53° to 25.53° which were highly considered to the other carbon allotropes with sp2 hybridized carbon atom hybridization structures. The higher pressure with added atmospheric air led to the excessive oxidation which influenced the growth of mCNT. Transmission electron microscopy (TEM) analysis observed mCNT filled by catalyst particles which suggested as magnetic phase induced the magnetic property of mCNT. The best electrical conductivity performance (lower electrical resistance) was owned by mCNT produced in the lower pressure condition with no air added.